The Construction of Edward Snowden as a Whistleblower in the New York Times and the Washington Post and How It Represents American Freedom of Speech - Cahyo Adi Nugroho (Universitas Sebelas Maret, 2020)
This article employs the media narratives and semiotics analytical approach to examine how Edward Snowden was constructed in online publications of the Times and the Post as two major national newspapers in the United States. The analysis finds that both media successfully construct Snowden positively as a new kind of leaker and as a hero in the sense that he brings back the importance of freedom of speech as a living myth in the United States. He is still viewed as a hero despite his moving to Russia, the political enemy of the United States. The analysis also shows that both media perpetuate the myth of free speech. They construct Snowden’s action positively as a new method to give people courage to criticize the government.